Is immunosuppressive therapy an effective treatment for COVID-19? – literature review - Ostrowska, Barbara; Kołodziejczyk, Kacper; Branewska, Justyna; Hop, Izabela; Matysek, Mikołaj; Olszanicka, Anna; Imioło, Jan; Maciąg, Anna; Niemiec, Rafał; Galas, Adam (Journal of Education, Health and Sport, 2023)
Introduction: The disease caused by SARS-CoV-2 is associated with a dysregulated immune response and a generalized inflammatory response. Therefore, during the search for effective therapy, attention was paid to drugs affecting and stabilizing such a response - tocilizumab, sarilumab, siltuximab, anakinra, baricitinib. Purpose of the work: Evaluation of the impact of immunosuppressant therapy on the course of the disease caused by the SARS-CoV-2 virus. Material and methods: The work was based on a review of available medical publications about immunosuppressive therapy for COVID-19 treatment. The literature in the PubMed and Google Scholar databases was searched based on the following keywords: tocilizumab, sarilumab, siltuximab, baricitinib, COVID-19, SARS-CoV-2, immunosuppressive therapy. Conclusion: Based on the analysis of the literature, the most effective therapeutic option seems to be tocilizumab. Promising alternatives may be sarilumab and siltuximab as they have the same target point of action. However, it is necessary to conduct further tests on their operation. The use of baricitinib may be useful, but probably only in certain circumstances. Anakinra proved to be much less effective. It should therefore be used with great caution.